2013
DOI: 10.3892/ol.2013.1593
|View full text |Cite
|
Sign up to set email alerts
|

Higher expression of circulating miR-182 as a novel biomarker for breast cancer

Abstract: MicroRNAs (miRNAs), present in the serum in a stable and reproducible manner, may be used as biomarkers for various diseases. Few studies have previously investigated circulating miRNAs in the peripheral blood of breast cancer (BC) patients. To identify the role of serum miR-182 levels in BC, the present study detected miR-182 levels in the serum of 46 BC patients and 58 controls, by quantitative PCR. The results showed that the serum miR-182 levels in BC patients were significantly higher compared with the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 38 publications
3
37
0
1
Order By: Relevance
“…This was also noted in a study on Lebanese FFPE breast cancer tissues [20,31]. miR-182 upregulation was noted in more than one study where its fold change of expression is usually more than 4 folds higher in cancerous breast tissue than in paracancerous tissue [32]. We found that the upregulation of miR-183 and miR-182 were positively correlated.…”
Section: Discussionsupporting
confidence: 85%
“…This was also noted in a study on Lebanese FFPE breast cancer tissues [20,31]. miR-182 upregulation was noted in more than one study where its fold change of expression is usually more than 4 folds higher in cancerous breast tissue than in paracancerous tissue [32]. We found that the upregulation of miR-183 and miR-182 were positively correlated.…”
Section: Discussionsupporting
confidence: 85%
“…Our data in human mammary cell line MCF10A shows that TGFβ inhibits miR-182, and, conversely, TGFβ inhibition increases miR-182, while neither TGFβ addition nor inhibition affects the abundance of miRNAs 146a and 146b (29) or miRNAs 181a and 181b (38), which also target BRCA 1 mRNA for degradation. The amount of miR-182 is increased in breast tumors compared with normal breast tissue (39) and in serum of patients with breast cancer (40). High miR-182 is associated with worse outcome in a meta-analysis of 10 studies (41).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of genes have been considered to involve in breast cancer. Research has shown that miRNA is directly related to the progression of the disease, having an inverse relationship in cancer patients (11). Oncogenic miR-155 is a well-established miRNA in many tumors, including breast cancer (12) where it can function as an oncogene to affect cancer development (13).…”
Section: Discussionmentioning
confidence: 99%